2020
DOI: 10.21203/rs.2.23238/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinctive nursing practices in working with mothers to care for hospitalised children at a district hospital in KwaZulu-Natal, South Africa: a descriptive observational study

Abstract: Background: The presence of family members and their active involvement in caring for hospitalised children is an established practice in many African paediatric settings, with family members often regarded as a resource. This aspect of African paediatric nursing practice lacks formal expression or a clear conceptual basis, and difficulties arise when applying concepts of family involvement originating from the culturally distinct practice environments of higher resourced settings including Europe and America.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“… In our work (North, Leonard, Bonaconsa, Duma, Coetzee, 2020) we have observed that the majority of children in hospital are accompanied by a female relative widely referred to as the child’s mother. Mother is therefore used to refer to any woman accompanying and caring for a child in hospital, whether or not they are the child’s biological mother or a grandmother, aunt, older sister or foster mother. …”
Section: Applying Nightingale Metrics: What Do Children’s Nurses Do?mentioning
confidence: 94%
“… In our work (North, Leonard, Bonaconsa, Duma, Coetzee, 2020) we have observed that the majority of children in hospital are accompanied by a female relative widely referred to as the child’s mother. Mother is therefore used to refer to any woman accompanying and caring for a child in hospital, whether or not they are the child’s biological mother or a grandmother, aunt, older sister or foster mother. …”
Section: Applying Nightingale Metrics: What Do Children’s Nurses Do?mentioning
confidence: 94%